Advances in Geosciences, 10 : Atmospheric Science (6-Volume Set). - Ip, Wing-Huen (World Scientific, 2009)
Advances in Geosciences is the result of a concerted effort to bring together the latest results and planning activities related to earth and space science in Asia and the international arena. The volume editors are all leading scientists in their research fields covering six sections: Atmospheric Science (AS), Hydrological Science (HS), Ocean Science (OS), Solid Earth (SE), Solar Terrestrial (ST) and Planetary Science (PS). The main purpose is to highlight the scientific issues essential to the study of earthquakes, tsunamis, atmospheric dust storms, climate change, drought, flood, typhoons.